The Attitude Changes Of Local Farmers Toward The Introduction Of Artificial Insemination In The Extensive Of Cattle Raising In The Seram Bagian Barat District, Maluku Province, Indonesia - Bambang Ngaji Utomo; NLP. Indi Dharmayanti; Muharam Saepulloh; Rahmat Setyo Adji; Procula Rudlof Matitaputty; Ermin Widjaja (Ilomata International Journal of Social Science, 2020)
Special efforts for cow must be pregnant (Upsus Siwab) is a program for the achievement of meat adequacy in 2022 through the optimization strategy of implementing Artificial Insemination (AI) in 34 provinces including Maluku Province. One of them is Seram Bagian Barat District. The type of cattle that are kept are Bali with extensive management. Maluku Province is The AI introduction area, so there are many challenges to meet the targets set. The purpose of this paper is to know the performance of AI introductions and the effect toward farmer attitudes in the SBB District during the 3 years of assistance. The method of this research was a survey, interviews with farmers, field officers, and district officers. Data with the Ishiknas format for 3 years was collected from the Agriculture services of SBB District. Data was tabulated and analyzed descriptively. The basic problems related to the application of AI are (1) it is difficult to detect the oestrus because all cattle are released, (2) the habits of mating cattle naturally, (3) there is no interest in participating of AI, and (4) the knowledge of oestrus is very minimal. The strategy to solved the problem was introduction the hormone of Oestrus Synchronization (SE). The strategy was quite successful, in 2017, the realization of AI was 85%. Realization in 2018 and 2019 were more than 100%. The S/C score was 1.13 times indicates that the cows have very good reproductive performance. There were 15 variations in gestational age with the range of 8 months 4 days - 9 months 17 days. The most average were 9 months 10 days (16.6%) and 9 months 11 days (16.6%). The pregnancy rates of AI was 10 -311 cows/month with an average of 108.8 cows, while in natural marriages 0 - 32 cows/month with an average of 12.5 cows. The birth weights of AI with Bali bulls straw ranged from 17 to 23 kg (an average of 19.6 kg), while the natural mating was an average of 16 kg. Another results, the birth weight of AI with Ongole bulls straw on male was an average of 32.2 kg and 30 kg on female. In 2017, the implementation of the AI was all done in combination with the SE because no farmers wanted to report the oestrus of cows. In 2018 there were reports from farmers and in 2019, all AI implementations were based on normal oestrus reports. The change in attitudes of farmers regarding adoption of AI was caused by the calves had a higher birth weight and a higher selling price. Implementation of AI in the District of SBB has good prospects for increasing the quantity and quality of cattle and also increasing the income of farmers